Cytotoxic effects of β-carboline alkaloids on human gastric cancer SGC-7901 cells - Fan, Yuxiang (Int J Clin Exp Med, 2015)
To investigate the cytotoxic effects of β-carboline alkaloids on human gastric cancer SGC-7901 cells. Human gastric cancer SGC-790s1 cells were treated with β-carboline alkaloids at the concentration of 0, 10, 20, 30 and 40 μg/ml for 48 hr. Cell viability was measured by Cell Counting Kit-8 assay. Cell apoptosis was detected by Hoechst 33258 staining and DNA fragmentation analysis. The expression of phosphatase and tensin homolog (PTEN) and extracellular signal-regulated kinase (ERK) was examined by quantitative real-time PCR (qRT-PCR) assay and western blot analysis. β-carboline alkaloids inhibited the growth of SGC-7901 cells concentration dependently. β-carboline alkaloids treated SGC-7901 cells displayed apoptotic nuclei as detected using Hoechst 33258 staining. β-carboline alkaloids also induced DNA ladder, indicative of apoptosis in SGC-7901 cells concentration-dependently. Furthermore, β-carboline alkaloids increased PTEN and decreased ERK mRNA expression in SGC-7901 cells in a concentration dependent manner. They also increased PTEN and decreased ERK protein expression. β-carboline alkaloids inhibit the growth and induce apoptosis of SGC-7901 cells. The cytotoxic effects of β-carboline alkaloids might correlate with increased PTEN expression and decreased ERK expression in SGC-7901 cells.